KEPENTINGAN AS BEKERJASAMA DENGAN TAIWAN DALAM BIDANG PERDAGANGAN PERSENJATAAN DI ERA GEORGE WALKER BUSH (2001-2009) - Reiza Andika S; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research analyzes US interest supporting and protecting Taiwan in conflict between Taiwan and China. In this case, The United States arms sales to Taiwan. The U.S. compelled to sell arms to Taiwan as a part of their trade relations, and to offset its trade deficits with Taiwan. Moreover, after the abrogation of Sino-American Mutual Defense Agreement, the U.S. could not leave Taiwan without any collateral security guarantee. The U.S. arms sales agreement to Taiwan was sealed in a policy named Taiwan Relations Act (TRA) on April 19, 1979. TRA marked as the first milestone in the history of the U.S. consistent and continued commitment to maintain the existence of and to provide a security defense for Taiwan, although it invites strong reactions from China. Even, in the reign of president George Walker Bush lead US , that is since 2001 until 2009, arms trade agreement between the United States to Taiwan reaches a value of 15 billion dollars U.S.The method used in this research is qualitative research. Some of the data obtained came from books, journals, articles, newspapers, the internet and other media. In this study also uses the perspective of realism, cooperation theory, the theory of International cooperation as a supported of the theory and use of the concept of national interest in seeing the cases studied.The research show that US have a s interest in assistance Taiwan in the conflict between Taiwan and China.Government of U.S come as international actor who have interest in Taiwan. United states become the state that protecting Taiwan. United State have interest to humanitarian and peacekeeping in Taiwan-China conflict. Behind this humanitarian and peacekeeping interest, US also have a economic and political interests in Taiwan.Keywords: U.S interests, Taiwan-China conflict, arms sales, George Walker Bus